THE USE OF INTESTINAL LAVAGE IN CHILDREN IN THE INTENSIVE CARE UNIT - M. V. Bykov; V. V. Lazarev; A. A. Ploskireva (SINAPS LLC, 2017)
In the process of intensive care in children under exigent infectious states  held a special method  of enteral detoxification salt enteral rastvorom - intestinal lavage. The method  was used in 75 children aged from 1,5 month  to 12 years with a body weight of 3.2 to 44 kg with various infectious pathologies, identifying 8 patients (10,6%) with pneumonia, ask for a ventilator, the translocation of intestinal microorganisms and microbiological confirmation enterohematic connection with the main pathological process is carried out 84 procedures. Positive clinical and laboratory effect was obtained in 70 patients, accounting for 93,31%.